Penerapan Advertising dan Digital Marketing Pada Warung Makan Indah Rasa - Wisnu Yuwono; Lia Willyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in a country's economic growth. However, some MSMEs still face obstacles in adopting digital marketing strategies and social media. This research focuses on Indah Rasa MSME and uses interview, observation, and documentation methods to collect data. The results of interviews with MSME owners identified problems and promotional strategies implemented. Observation techniques were used to understand field conditions, while documentation recorded historical data and MSME activities. The adoption of digital marketing strategies by MSMEs is important to improve competitiveness, but challenges related to knowledge, concerns over data security, and limited access to resources still need to be addressed. This research provides an in-depth insight into the data collection efforts and techniques used to understand the challenges and opportunities for MSMEs in implementing digital marketing